Nutritional Care for Patients with Ebola Virus Disease in Ebola Treatment Units – Past and Current Experiences from Practitioners - Ververs, Mija; Anantharam, Puneet (International Journal of Nutrition, 2019)
Background In November 2014, the World health Organization (WHO), in collaboration with United Nations Children's Fund (UNICEF), and the World Food Programme, produced interim guidelines (iGL) on providing nutritional support to patients in Ebola treatment units (ETUs). They have been translated into French and issued by the Ministry of Health, UNICEF and WHO in adapted versions to be used in the current outbreak in the Democratic Republic of the Congo (DRC). This paper evaluates the use and usefulness of the 2014 iGL in the West Africa and current DRC Ebola virus disease (EVD) outbreaks and identifies experiences and lessons learned from practitioners on the operational aspects of nutritional care and support in ETUs. Methods Key-informants (n=26), from 12 organizations (Non-Governmental Organizations, United Nations, Red Cross Red Crescent Movement) were interviewed who were actively engaged in the nutritional and/or clinical care of EVD patients. Results There was a consensus among key-informants that the 2014 iGL initially served a guiding purpose. However, the vast amount of learning from the 2014-2016 and current EVD outbreaks indicates that the interim guidelines need to be revised. Practitioners struggled to find operational solutions for nutritional care, and the challenges were plentiful, especially regarding 1) the different perceptions of the importance of nutritional care among ETU staff; 2) the difficulties around food preparation and distribution for EVD patients; 3) how to take into account the patients’ dietary preferences; 4) the nutritional care needed in relation to specific EVD symptoms; 5) who assumed roles in nutritional care in ETUs; 6) if and how feeding support was organized; 7) whether malnutrition needed to be addressed and how; and 8) whether the intake of specific nutrients could contribute to improved treatment outcomes.  Information from the key-informants interviews resulted in numerous lessons learned and recommendations for nutritional support during current and future outbreaks. Conclusions This investigation underscored the importance of documenting experiences of practitioners on nutritional care in emerging infectious diseases for which limited scientific evidence exists and for which interim guidelines are produced to fill in knowledge gaps. It also emphasized the importance of nutritional care in ETUs during treatment.
Keywords: Ebola Virus Disease; Nutritional Care; Ebola Treatment Units; Malnutrition; Nutritional Support; Interim Guidelines